Representation and exceeding the powers of bodies of an entrepreneurial company: issues of theory and law application (Law and Safety, 2025)
The article supports the view that acquisition of civil rights and obligations by a legal entity is conditioned, in particular, by its own bodies of will expression, and the ability to be independently liable with all its property is conditioned by the actual availability of such property which could be recovered if necessary.The author argues that corporate disputes regarding invalidation of transactions made by officials of business entities in excess of their authority constitute one of the most common categories within corporate relations. The essence and specificity of such disputes is that, in cases stipulated by regulations, officials alienate company property in favour of third parties on terms unfavourable to the company without obtaining the consent of the general meeting or supervisory board (if established) of such a legal entity.The author proves that in order to invalidate a transaction concluded by an official of a business entity in excess of his/her authority, this legal entity, in addition to the arguments for such “excess”, must prove bad faith on the part of the counterparties and their awareness of the excess of authority by the company’s representative, as well as the existence of grounds to conclude that the participation of a third party in the transaction was formal and aimed at unlawful deprivation of property of such a company (in other circumstances, the company risks having its claim dismissed or a favourable decision cancelled at the stage of appeal).This circumstance is the basis for invalidation of this transaction only at the company's claim or a claim filed to secure its interests. The above calls for expanded use of the shareholder's right to file a derivative claim in the interests of the company to invalidate a transaction made by an official of a company’s body in excess of the powers granted to him/her within the framework of law enforcement.